How trust influence social capital to support collective action in agroforestry development? - ROMMY QURNIATI; INDRA GUMAY FEBRYANO; DINI ZULFIANI (Society for Indonesian Biodiversity, 2017)
Qurniati R, Febryano IG, Zulfiani D. 2017. How trust influence social capital to support collective action in agroforestry development?. Biodiversitas 18: 1201-1206. Trust is an important factor for strengthening social capital. Trust in forest community is achieved through collective action in small scale agroforestry. It was challenging process regards the low on social capital in communities. This study intended to analyse and explain how trust influences social capital in encouraging collective action in agroforestry development. The study conducted in Sidodadi and Sumur Kumbang Lampung Province, from October-December 2016. The area was selected based on disparities of sea level of villages. The data collected through in-depth interviews with several members of farmer group who responsible for agroforestry. The research found that trust between farmer group member remains high. However, trust as a source of social capital was not supported collective action since farmer group institution is weak. Therefore, to support agroforestry development, social capital should be increased through the development of good networks (bridging) to reach collective goal i.e. community welfare and sustainable forest management